Welfare-to-Work, Wages and Wage Growth - Ian Walker; Reamonn Lydon (Institute for the Study of Labor (IZA), 2004)
This paper attempts to uncover the effects of a welfare-to-work programme that acts as a wage subsidy on wage growth by exploiting an expansion to this welfare programme in the UK. The conventional wisdom is that such programmes trap recipients into low wage, low quality work – this comes from the simple argument that the ?poverty trap?, which a wage subsidy for low income workers induces, reduces the benefits to on-the-job training and so reduces wage growth. In fact, a wage subsidy will also reduce the costs of general training because we would normally expect workers to pay for their own general training in the form of lower gross wages. So a wage subsidy is a way of sharing these costs with the taxpayer. Thus, the net effect on wage progression depends on whether it reduces costs by more or less than it reduces the benefits. The paper uses Labour Force Survey panel data to look at wage levels and growth in the UK before and after Working Families? Tax Credit (WFTC) replaced Family Credit (FC). We exploit nonlinearities in the system and overall, we find that wage growth for those on WFTC exceeded wage growth for those on FC, although for those already on the programme wage growth declined, reflecting the fact that under WFTC the wage growth is implicitly taxed over a wider range of wages.
Keywords: I38; J30; 330; wage growth; welfare-to-work; Workfare; Lohnsubvention; Lohn; Schätzung; Grossbritannien